THE INFLUENCE OF WORK MOTIVATION, COMMUNICATION AND ORGANIZATIONAL STRUCTURE ON ORGANIZATIONAL CULTURE AND EMPLOYEE PERFORMANCE IN BAPPEDA, SOUTH BARITO REGENCY - John Apriadi; Musthafa, Musthafa (INFOKUM, 2020)
This study aims to determine and analyze the effect of work motivation, communication and organizational structure on organizational culture and employee performance at Bappeda, South Barito Regency. The research object is the employees at Bappeda South Barito Regency, as many as 83 employees consisting of 47 civil servants and 36 non-civil servants. Determination of the sample in this study using saturated samples, where the population as well as samples. The independent variables in this study are Work Motivation, Communication and Organizational Structure, Organizational Culture as an influencing variable, while the dependent variable is Employee Performance. The analysis technique used is the path analysis equation analysis. The path analysis equation shows that the path coefficient is varied, based on the results of the analysis, it can be concluded that most of the independent variables studied have a significant effect on the dependent variable. The results showed that: (1) Work motivation has a positive and significant effect on organizational culture variables. (2) Communication has a negative and significant effect on Organizational Culture variables. (3) Organizational structure has a positive and significant effect on Organizational Culture. (4) Work Motivation has no significant effect on Employee Performance variables. (5) Communication has a positive and significant effect on Performance variables. Employees. (6) Organizational Structure has a positive and significant effect on Employee Performance. (7) Organizational culture has a negative and insignificant effect on employee performance variables, employees at Bappeda, South Barito Regency.